Collaborative intercultural activities to enhance speaking skills. (2022)
The goal of this project is to create an innovative pedagogical proposal to improve the EFL learners’ speaking skills through collaborative intercultural activities. This proposal follows the guidance and components of a didactic sequence considering the collaborative learning’s stages together with the Byram’s components from the intercultural communication model. The methodology that guides this proposal is through the collaborative learning stages and the intercultural communication models from Byram (1997) and Munezane (2019). It is expected that students can improve their speaking skills in terms of fluency, accuracy, and vocabulary. But also, developing collaborative and intercultural skills while interacting and discussing during each lesson plan which could allow them to know more about their own culture and other’s English cultures